Residual monomer of reline acrylic resins - Effect of water-bath and microwave post-polymerization treatments - Urban, Vanessa M.; Machado, Ana Lucia [UNESP]; Oliveira, Regina V.; Vergani, Carlos Eduardo [UNESP]; Pavarina, Ana Claudia [UNESP]; Cass, Quezia B. (Elsevier B.V., 2007)
Objectives. This study compared the residual monomer (RM) in four hard chair-side reline resins (Duraliner II-D, Kooliner-K, Tokuso Rebase Fast-TRF and Ufi Gel hard-UGH) and one heat-polymerized denture base resin (Lucitone 550-L), which was processed using two polymerization cycles (short-LS and long-LL). It was also investigated the effect of two after polymerization treatments on this RM content.Methods. Specimens (n = 18) of each material were produced following the manufacturers' instructions and then divided into three groups. Group I specimens were left untreated (GI-control). Specimens of group II (GII) were given post-polymerization treatment by microwave irradiation. In group III (GIII), specimens were submitted to immersion in water at 55 degrees C (reline resins-10 min; denture base resin L-60min). The RM was analyzed using high performance liquid chromatography (HPLC) and expressed as a percentage of RM. Data were analyzed by two-way ANOVA followed by Tukey's test (alpha = 0.05).Results. Comparing control specimens, statistical differences were found among all materials (p < 0.05), and the results can be arranged as K (1.52%) > D (0.85%) > UGH (0.45%) > LL (0.24%) > TRF (0.14%) > LS (0.08%). Immersion in hot water (GIII) promoted a significant (p < 0.05) reduction in the RM for all materials evaluated compared to control (GI), with the exception of LL specimens. Materials K, UGH and TRF exhibited significantly (p < 0.05) lower values of RM after microwave irradiation (GII) than in the control specimens.Significance. The reduction in RM promoted by water-bath and microwave post-polymerization treatments could improve the mechanical properties and biocompatibility of the relining and denture base materials. (c) 2006 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: acrylic resin; residual monomer; post-polymerization treatment; HPLC